Challenges in the management of a child with yolk sac tumour of the nasal cavity presenting with epistaxis and progressive respiratory distress - Mohd Nor, Khadijah; Manuel, Anura Michelle; Chew, Man Fong; Gan, Chin Seng; Yap, Tsiao Yi; Loong, Siow Ping; Abdullah, Wan Ariffin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Yolk Sac tumour (YST) of the nasal cavity is extremely rare with only less than five previously reported cases in the English literature. Due to its rarity, the diagnosis is not one that is considered at initial presentation until tissue biopsies are sent for histopathological examination. Serum α-fetoprotein levels aid in diagnosis and in monitoring progression of the tumour. Being a very uncommon tumour of germ cell origin presenting as localized disease in the nasal cavity, prognosis and survival rates are difficult to determine. We are reporting a rare yolk sac tumour case in an infant and the challenges encountered in its management.